Les douze circonscriptions électorales « privilégiées » du Québec - Bonenfant, Jean-Charles (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
Article 80 of the British North America Act expressly disallows any modification of the boundaries of twelve of the electoral districts of the province of Québec (all located in the Eastern Townships and along the north shore of the Ottawa River) without the majority consent of the deputies representing these districts. In 1867 the districts were predominantly English-speaking but most now contain a French-speaking majority. The author traces the history of application of Article 80 from 1867 to the present, and by citing numerous boundary changes that have occurred shows that the Article has been more honoured in the breach than the observance. The author concludes that the Article is obsolete and antidemocratic. He then outlines some of the procedural difficulties involved in a possible repeal of the Article.